2023
DOI: 10.1101/2023.03.12.532289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanopore sequencing for the 17 modification types in 36 locations inE. coliribosomal RNA enables monitoring of stress-dependent changes

Abstract: Escherichia coli possess the 16S and 23S rRNA strands that have 36 chemical modification sites with 17 different structures. Direct RNA nanopore sequencing using a protein nanopore sensor and helicase brake, which is also a sensor, was applied to the rRNAs. Nanopore current levels, base calling profile, and helicase dwell times for the modifications relative to non-modified synthetic rRNA controls found signatures for nearly all modifications. Signatures for clustered modifications were determined by selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…12,52 The occupancy of Ψ across the transcriptome is organism, cell-type, and stress-dependent, suggesting that this U isomer has a significant role in cellular processes. 4,12,22,23,37 Determination of these roles will require accurate and quantitative sequencing of RNA, in which nanopore direct RNA sequencing is a candidate method to achieve this goal. 37,53 Our work identified that nanopore signatures for Ψ are highly sequence context dependent and that using a consensus of nanopore current, helicase dwell time, and base miscalling is an approach to sequence this U isomer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,52 The occupancy of Ψ across the transcriptome is organism, cell-type, and stress-dependent, suggesting that this U isomer has a significant role in cellular processes. 4,12,22,23,37 Determination of these roles will require accurate and quantitative sequencing of RNA, in which nanopore direct RNA sequencing is a candidate method to achieve this goal. 37,53 Our work identified that nanopore signatures for Ψ are highly sequence context dependent and that using a consensus of nanopore current, helicase dwell time, and base miscalling is an approach to sequence this U isomer.…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli rRNA strands provide a test case for this question because there are 36 well-established modification sites in the 16S and 23S rRNAs with 17 different chemical structures. 4 These RNAs are modified with methyltransferases, isomerases, an oxidase, or a reductase to generate the 17 different structures (see Figure 5a for acronyms and locations of the modifications). The rRNAs were extracted from the stationary phase grown E. coli that have the modifications written at high occupancy based on mass spectrometry analysis.…”
Section: Extension To 17 Modifications In Ribosomal Rnamentioning
confidence: 99%
“…Many different epitranscriptomic modifications have been sequenced with the nanopore system. 14–17 The present discussion will focus on the uridine isomer pseudouridine (Ψ) because the prior work showcases the strengths and challenges of this approach (Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%
“…27 In nanopore direct RNA sequencing for Ψ, this modification is “miscalled” as a C with the highest frequency, and miscalls to the other bases occur with lower frequencies 16,18–25 Natural U/C sequence variations will present as Ψ in base-call data analyses. These base miscall signatures have allowed sequencing for Ψ directly in rRNA, 17,18,25 mRNA, 20,23,25 tRNA, 14,15 and vRNA 19 that can have lengths >5000 nts, demonstrating the ability for long-read modification-aware sequencing with this method. A challenge to using base-called data for quantitative analysis of Ψ is that the frequency of “miscalls” is sequence-context dependent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation